Lucea, Hanover, Jamaica - Survey Department, Jamaica BWI. (Jamaica : Survey Department, Jamaica, 1959)
This map shows sections of Lucea as well as, its harbour.
These maps are digitized.
Keywords: Country maps. -- Maps. -- Jamaica